Regulated protein turnover: snapshots of the proteasome in action - Bhattacharyya, Sucharita (Nat Rev Mol Cell Biol, 2014)
The ubiquitin-proteasome system (UPS) is the main ATP-dependent protein degradation pathway in the cytosol and nucleus of eukaryotic cells. At its centre is the 26S proteasome, which degrades regulatory proteins and mis-folded or damaged proteins. In a major breakthrough, several groups have determined high-resolution structures of the entire 26S proteasome particle in different nucleotide conditions and with and without substrate using cryo-electron microscopy combined with other techniques. These structures bring some surprising insights into the functional mechanism of the proteasome and will provide invaluable guidance for genetic and biochemical studies of this key regulatory system.